Solute rotation and solvation dynamics in deep eutectic solvents - Sk Saddam Hossain; Anunay Samanta (Chemical Physics Impact, 2021)
Deep eutectic solvents (DESs) have emerged in recent years as novel environment-friendly non-conventional media for a variety of applications. In order to realize the full potential of this promising class of substances as solvents, an in-depth knowledge of the solution structure, dynamics and various interactions operating in these liquids is very crucial. In this mini-review we highlight the findings of some recent time-resolved fluorescence studies, which provide insight into the structural and dynamical features of these media. Specifically, we discuss how the dynamics of rotation of some selected fluorescence probe molecules and solvent reorganization around them in these solvents are influenced by the nature and structural elements of the solvent constituents, additives, and external parameters and the findings provide an understanding of the microscopic picture of the structure and dynamics of these complex media. At the end, we outline the scope and need of further work to obtain additional clarity on the physicochemical properties of these substances and to broaden their applications.